Attainment of Metabolic Goals in the Integrated UK Islet Transplant Program With Locally Isolated and Transported Preparations. Issue 12 (1st October 2013) - Brooks, A. M.; Walker, N.; Aldibbiat, A.; Hughes, S.; Jones, G.; de Havilland, J.; Choudhary, P.; Huang, G. C.; Parrott, N.; McGowan, N. W. A.; Casey, J.; Mumford, L.; et al.
Abstract The objective was to determine whether metabolic goals have been achieved with locally isolated and transported preparations over the first 3 years of the UK's nationally funded integrated islet transplant program. Twenty islet recipients with C‐peptide negative type 1 diabetes and recurrent severe hypoglycemia consented to the study, including standardized meal tolerance tests. Participants received a total of 35 infusions (seven recipients: single graft; 11 recipients: two grafts: two recipients: three grafts). Graft function was maintained in 80% at [median (interquartile range)] 24 (13.5–36) months postfirst transplant. Severe hypoglycemia was reduced from 20 (7–50) episodes/patient‐year pretransplant to 0.3 (0–1.6) episodes/patient‐year posttransplant (p < 0.001). Resolution of impaired hypoglycemia awareness was confirmed [pretransplant: Gold score 6 (5–7); 24 (13.5–36) months: 3 (1.5–4.5); p < 0.03]. Target HbA1c of <7.0% was attained/maintained in 70% of recipients [pretransplant: 8.0 (7.0–9.6)%; 24 (13.5–36) months: 6.2 (5.7–8.4)%; p < 0.001], with 60% reduction in insulin dose [pretransplant: 0.51 (0.41–0.62) units/kg; 24 (13.5–36) months: 0.20 (0–0.37) units/kg; p < 0.001]. Metabolic outcomes were comparable 12 months posttransplant in those receiving transported versus only locally isolated islets [12 month stimulated C‐peptide: transported 788 (114–1764) pmol/L (n = 9); locally isolated 407 (126–830) pmol/L (n = 11); p = 0.32]. Metabolic goals have been attained within the equitably available, fully integrated UK islet transplant program with both transported and locally isolated preparations.